Ihsan in Study, Iffah in Usage: An Islamic Perspective on Self-Regulated Learning and Social Media Addiction in Muslim University Student In Indonesia - Ade Ubaidah (Journal of Innovative and Creativity, 2026)
The increasing prevalence of social media addiction among university students poses a serious challenge in higher education. This study aims to examine the role of self-regulated learning (SRL) in reducing the level of social media addiction among Muslim students. The results of a simple linear regression analysis indicate that SRL has a significant negative effect on social media addiction (β = -0.222, p = 0.010). This means that students with higher levels of SRL tend to have lower tendencies toward social media addiction. From an Islamic perspective, SRL can be seen as a manifestation of iffah (self-restraint), which is the ability to guard oneself from distractions and unproductive behavior. Strengthening SRL may serve as a form of mujahadah (spiritual struggle) in developing a Muslim's iffah, as an effort to preserve intellectual dignity and time within academic activities. Thus, SRL impacts not only academic performance but also reflects the integration of Islamic moral values in responding to today’s digital challenges.